2020
DOI: 10.1051/e3sconf/202021803012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Buyang Huanwu Decoction in Treating Sequelae of Stroke

Abstract: Objective: To explore the clinical effect of applying Buyang Huanwu Decoction in the treatment of sequelae of stroke. Methods: The research work was carried out in our hospital, which was from November 2018 to November 2019. A total of 200 patients were selected for treatment during this period, all of whom were patients with sequelae of stroke, and 100 patients were grouped randomly. One group was given conventional acupuncture treatment as the control group, and the other group was given acupuncture combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…By studying the changes in symptoms and various scale scores of 100 patients with post-stroke sequelae after four weeks of treatment, Jie Hu [8] showed that the Buyang Huanwu Decoction is indispensable in assisting in the treatment of post-stroke sequelae, and it can help patients to enhance their self-care ability and have a great improvement in their quality of life. By studying the pharmacology of some of the Chinese medicines in the Buyang Huanwu Decoction, Xingwen Pi [9] showed that the components of certain Chinese medicines in the Buyang Huanwu Decoction have targeted therapeutic effects on post-stroke sequelae. Tianlei Wang [10] randomly grouped 78 patients with post-stroke sequelae, and found that the treatment of Buyang Huanwu Decoction with electroacupuncture was able to reduce the expression rate of inflammatory factors and promote the recovery of limb motor function by comparing the indexes and data analysis of the two groups.…”
Section: Application Of Buyang Huanwu Decoctionmentioning
confidence: 99%
“…By studying the changes in symptoms and various scale scores of 100 patients with post-stroke sequelae after four weeks of treatment, Jie Hu [8] showed that the Buyang Huanwu Decoction is indispensable in assisting in the treatment of post-stroke sequelae, and it can help patients to enhance their self-care ability and have a great improvement in their quality of life. By studying the pharmacology of some of the Chinese medicines in the Buyang Huanwu Decoction, Xingwen Pi [9] showed that the components of certain Chinese medicines in the Buyang Huanwu Decoction have targeted therapeutic effects on post-stroke sequelae. Tianlei Wang [10] randomly grouped 78 patients with post-stroke sequelae, and found that the treatment of Buyang Huanwu Decoction with electroacupuncture was able to reduce the expression rate of inflammatory factors and promote the recovery of limb motor function by comparing the indexes and data analysis of the two groups.…”
Section: Application Of Buyang Huanwu Decoctionmentioning
confidence: 99%